MENDORONG KESADARAN KESEHATAN MENTAL MELALUI KEGIATAN SAGITA RUN - Mulia, Fernando; Christi , Natalia; Evangelique, Michaella; Zanitta , Gabriella Laeticia Alma (Universitas katolik Musi Charitas, 2025)
Purpose: This community engagement initiative was implemented to enhance public awareness of mental health and healthy lifestyles, particularly in response to the rising prevalence of non-communicable diseases (NCDs) and psychological stress in urban environments. Design/Methodology/Approach: A community-based participatory approach was employed, involving collaboration among students, faculty members, and local residents in Bandung. The program, known as SAGITA Run, was designed as an inclusive recreational running event integrated with health education. Digital tools such as Google Forms and promotional platforms including WhatsApp and social media were utilized to facilitate registration, coordination, and participant engagement. Findings: The activity attracted 150 participants. Post-event surveys (n = 51) indicated that 100% of respondents reported increased awareness of healthy living practices, while 98% perceived direct health benefits. Moreover, all respondents expressed willingness to participate in future editions of the event. Practical Implications: The implementation of SAGITA Run illustrates the effectiveness of low-cost, student-led initiatives in delivering public health education. It also provides students with meaningful service-learning experiences that promote both civic engagement and academic integration. Originality/Value: This program offers a replicable model for higher education institutions seeking to align academic learning with community needs, contributing directly to the realization of Sustainable Development Goal 3 (Good Health and Well-Being).